EFFECT OF THE FLOW CONDITIONS AND VALVE SIZE ON BUTTERFLY VALVE PERFORMANCE - (:unkn) unknown (TURKISH SOC THERMAL SCIENCES TECHNOLOGY, 2010)
In the present work, two different sizes butterfly valves, DN65 and DN80, were tested according to standard testing method ANSI/ISA-75.02-1996. The tests were performed at different flow rates such as 2, 3 and 4 m/s and at different valve opening angles such as 0, 10, 20, 30 and 40 degrees. The opening angle 0 degrees was considered as the fully open valve. The flow area percentages, phi, were calculated for different valve openings as 100, 82.64, 65.80, 50 and 35.72% and pressure drops, Delta P, were recorded for different valve openings at different velocities. Using the experimental data the loss and flow coefficients, K and (C) under bar ((v) under bar), were calculated and correlations were proposed to give K and C(v) as a function of the flow area percentage, phi. Uncertainty analysis was performed to show the effect of the measurement uncertainties on the performance coefficients. The proposed correlations provide an effective way to determine the performance coefficients of two different sizes of butterfly valves. This approach can be applied to other valves for determining their performance.
Keywords: Butterfly valve; Loss coefficient; Flow coefficient; Uncertainty analysis